Mongolia 2020 Poverty Report : A Decade of Progress and Stagnation in Poverty Reduction - World Bank (Washington, DC, 2022)
Mongolia made notable strides in reducing poverty from 2010 to 2014, but the pace of poverty reduction slowed significantly after the 2016 economic recession. The trend of declining inequality and inclusive growth seen in the first half of the decade changed course in the latter half. Greater urbanization and narrowing geographical disparities in poverty have meant that the poor have become increasingly concentrated in urban centers, especially Ulaanbaatar. Economic volatility and uncertainty together with restrictions on face-to-face services may have led to an increase in precautionary saving among households, particularly during the Coronavirus disease 2019 (COVID-19) pandemic. An additional issue related to the measurement of consumption in 2020 specifically is the survey-to-survey imputation approach that was used to estimate poverty and the consumption distribution due to changes in the household socio-economic survey (HSES) questionnaire. Finally, despite significant increases, social transfers have had only modest success in reducing poverty due to targeting inefficiencies. The 2020 HSES shows that impacts to employment in 2020 were not significant until the final quarter, with workers in urban areas and in the service sector more likely to be affected. While subsequent surveys will provide a clearer picture of the longer-term impacts of the pandemic, signs of potentially lasting and unequalizing effects have emerged after 2020.